Longitudinal study of the spectral composition of behavioral rhythms in the rat - Castro, ECV; Andrade, MMM (Taylor & Francis Ltd, 2005)
Four. male Wistar rats were housed in pairs of siblings, on LD 12:12h and 22 degrees C + 2 degrees C. Food and water were provided ad libitum. Behavior was videotaped from the 1st to the 3rd month of life. In each age-bracket the spectral composition of rhythmic expressions of the following behavioral categories was analyzed: rest, eat, drink, cage exploration, self-grooming, and social interaction. Rats maintained a stable rank order of time engaged in different behaviors through development, despite modification of time spent in grooming, drinking and social interaction as they got older. Spectral composition of behaviors followed a general ontogenetic pattern: ultradian frequencies of 12-h and 8-h were the strongest in the 1st month and circadian periodicity was predominant in the 3rd month. The increase of circadian power compared with ultradian power components agrees with literature findings. To our knowledge, self-grooming and social interaction have not been investigated before in this context. The similarities between siblings suggest the mutual influence of partners and/ or the existence of genetic factors. Ongoing studies are examining the importance of the social surroundings in which animals develop to the acquisition of adult rhythmic pattern.
Keywords: ontogeny; behavioral rhythms; rat; circadian rhythm; spectral analysis